2022
DOI: 10.1002/apj.2768
|View full text |Cite
|
Sign up to set email alerts
|

High‐performance Sn‐based anode with robust lignin‐derived hard carbon support for sodium‐ion batteries

Abstract: Tin anode has great potential for sodium-ion batteries owing to its high theoretical capacity, but its tremendous volume expansion during the sodium (de)alloying processes leads to the structural degradation and cycling instability. Herein, we report a new design strategy by using low-cost enzymatic hydrolysis lignin-derived hard carbon as an ideal support for Sn particles dispersion. Sn can be uniformly anchored on the robust carbon substrate, to efficiently relieve Sn volume expansion upon cycling. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…To achieve good cyclability with a Sn anode (91% of capacity retention after 1000 cycles) Wang et al employed lignin as a precursor to form Sn/C particles. 136 Similar approaches could be investigated to enable different alloying metal anodes for high energy density SIBs and KIBs in the future.…”
Section: Lignin For Energy Applications – Batteriesmentioning
confidence: 99%
“…To achieve good cyclability with a Sn anode (91% of capacity retention after 1000 cycles) Wang et al employed lignin as a precursor to form Sn/C particles. 136 Similar approaches could be investigated to enable different alloying metal anodes for high energy density SIBs and KIBs in the future.…”
Section: Lignin For Energy Applications – Batteriesmentioning
confidence: 99%
“…The N, P co‐doped hard carbon microspheres provided a specific capacity of 248 mAh g −1 for 200 cycles at 0.1 A g −1 with a retention rate close to 92.2% (Figure 13b,c). Wang et al [ 113 ] uniformly loaded Sn particles with high theoretical capacity on the lignin carbon substrate. The results showed that the hard carbon substrate could effectively dilute the aggregation effect of Sn nanoparticles and buffer the volume expansion of Sn during charging/discharging.…”
Section: Application Of Lignin Carbons In Electrochemical Energy Storagementioning
confidence: 99%
“…Lignin has more than 60% carbon content, with the majority existing in the form of an aromatic structure. [40,41] Oxygen elements, which mostly exist in the form of functional groups in cellulose, hemicellulose, and lignin, can significantly enhance the molecular activity of these three compounds. Utilizing lignocellulosic biomass as precursors not only reduces the exposure of synthesis processes to chemicals but also facilitates the potential of commercializing current developed technologies of producing CDs.…”
Section: Introductionmentioning
confidence: 99%